DIALECTICS OF RELIGIOUS MODERATION AND RELIGIOUS LIFE DURING THE ENFORCEMENT OF PUBLIC ACTIVITY RESTRICTION (PPKM) IN BANDAR LAMPUNG CITY - Idrus Ruslan; Muhammad Candra Syahputra; Luthfi Salim (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
The COVID-19 pandemic has changed the life of the world community. The handling of COVID-19 in Indonesia influenced many different aspects of people's lives, including the religious life of the community. PPKM (the Enforcement of Public Activity Restrictions) influenced people's religious lives in Indonesia, particularly in the city of Bandar Lampung. During the implementation of PPKM, the authors of this study conducted research on the religious dynamics of the inhabitants of Bandar Lampung. This study is a field study with a qualitative methodology. The researchers gathered the data for this research through observation, interviews, and documentation. According to the findings of this study, the implementation of the PPKM generates religious dynamics in the city of Bandar Lampung, such as passive religious activities in worship places such as churches, mosques, and temples, the implementation of strict health protocols during religious holidays, and the adjustment of all religious activities in Bandar Lampung. Looking at these difficulties, a moderate approach can be a solution to the religious dynamics that transpired in Bandar Lampung during the PPKM. Religious people with a moderate mindset will put communal interests over personal ones. Obeying PPKM policies is a form of prioritizing common interests for mutual safety so that the community can avoid the covid-19 outbreak.